Sustainable Communication: Cross-Cultural Management of Higher Education Staff in East Coast of Peninsular Malaysia - Isma Rosila Ismail; Che Hasniza Che Noh; Zaleha Mohamad (International Journal of Business, Economics, and Social Development, 2020)
This study investigates the ethnic and cultural backgrounds of the University Malaysia Terengganu (UMT) personnel to determine the elements of uncertainty avoidance among the staff. As such, the study examines the respondents’ expectations of rules, changes, and creativity in uncertainty avoidance. This study also investigates the differences between respondents’ behaviour in High Uncertainty Avoidance (HUA) or Low Uncertainty Avoidance (LUA) and the extent to which these differences affect communication. Furthermore, this study employed mixed (qualitative and quantitative) methods as a research design, with ethnography as a research approach.  The study data were analysed using the Statistical Package for Social Science (SPSS Version 20) and thematic analysis for an in-depth exploration of the respondents. The result of the study showed that, regardless of ethnicity, common HUA values were shared in the observation of rules and regulations, which reflected the consensual agreement on the importance of observing rules. Concerning changes and adaptation, all the three ethnic groups indicated LUA, with only a small number indicating HUA in this matter. The Malay personnel indicated an especially high LUA, as the future was believed to be too intricate, ambiguous, unpredictable, and hostile for efficient planning. Regarding workplace creativity, all three ethnic groups indicated LUA, with only a small number indicating HUA in this matter. Nevertheless, it is made aware in this study that the results are not representative of the three ethnic populations in Malaysia.